Bernini's beloved: a portrait of Costanza Piccolomini - McPhee, Sarah (Yale University Press, 2012)
The bust -- Costanza Piccolomini: Zitella Da Viterbo -- Master of the world -- Two letters -- Matteo Scultore -- Costanza Scultora -- The garden at the four fountains -- Bernini's beloved